Pharmaceutical Cocrystals: New Solid Phase Modification Approaches for the Formulation of APIs - Anna Karagianni; Maria Malamatari; Kyriakos Kachrimanis (MDPI AG, 2018)
Cocrystals can be used as an alternative approach based on crystal engineering to enhance specific physicochemical and biopharmaceutical properties of active pharmaceutical ingredients (APIs) when the approaches to salt or polymorph formation do not meet the expected targets. In this article, an overview of pharmaceutical cocrystals will be presented, with an emphasis on the intermolecular interactions in cocrystals and the methods for their preparation. Furthermore, cocrystals of direct pharmaceutical interest, along with their in vitro properties and available in vivo data and characterization techniques are discussed, highlighting the potential of cocrystals as an attractive route for drug development.